2008
DOI: 10.1200/jco.2007.13.2043
|View full text |Cite
|
Sign up to set email alerts
|

High Viral Load and Hepatitis B Virus Subgenotype Ce Are Associated With Increased Risk of Hepatocellular Carcinoma

Abstract: High HBV DNA level and HBV genotype C, particularly subgenotype Ce, increased the risk of HCC in chronic hepatitis B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
239
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(254 citation statements)
references
References 32 publications
11
239
3
1
Order By: Relevance
“…Yang et al [6] reported that the incidence of HCC was significantly higher in those who were HBsAg and HBeAg positive than in those who were HBsAg positive only. Recently, this was confirmed by showing a correlation between baseline HBV DNA levels in asymptomatic adult HBsAg carriers and the risk of HCC [10][11][12][13].…”
Section: Hepatitis B Infectionmentioning
confidence: 82%
“…Yang et al [6] reported that the incidence of HCC was significantly higher in those who were HBsAg and HBeAg positive than in those who were HBsAg positive only. Recently, this was confirmed by showing a correlation between baseline HBV DNA levels in asymptomatic adult HBsAg carriers and the risk of HCC [10][11][12][13].…”
Section: Hepatitis B Infectionmentioning
confidence: 82%
“…Ascites was defined as free peritoneal fluid identified by ultrasound or computed tomography scans, or as clinically evident ascites confirmed by paracentesis. SBP was defined as an ascitic fluid polymorph count of 250/ mm 3 or above with or without positive bacterial culture. Variceal bleeding was defined as hematemesis and/ or melena, with esophageal or gastric varices identified during upper gastrointestinal endoscopy, and no other lesion that might explain the bleeding episode.…”
Section: Methodsmentioning
confidence: 99%
“…1 A high level of hepatitis B virus (HBV) DNA has been consistently shown to be an independent risk factor for the development of cirrhosis and HCC. 2,3 Antiviral therapy is effective in suppressing HBV DNA and reducing the risk of hepatic events and HCC. 4,5 Lamivudine, the first generation oral nucleoside analogue was shown to reduce the incidence of hepatic events in patients with advanced fibrosis or compensated cirrhosis by 50%.…”
mentioning
confidence: 99%
“…17,18 Therefore, persistent suppression of the HBV-DNA, ideally at an undetectable level or, at least, at a level of 2,000 UI/mL (10,000 copies/mL), is another acceptable marker for treatment response. In studies that analyzed treatment with lamivudine in HBeAgnegative patients or those with advanced liver fibrosis, sustained viral suppression was associated with the decrease in complications of cirrhosis and hepatocellular carcinoma.…”
Section: Viral Suppression Of Hbv-dnamentioning
confidence: 99%